Theoretical foundations of interaction between public administration bodies and civil society institutions - Myrna, Nadiya; Stasiuk, Oleksandr (Theory and Practice of Public Administration, 2024)
This article examines the theoretical foundations of interaction between public administration bodies and civil society institutions in the context of Ukraine’s democratic transformation.The essential characteristics of «public administration» and «civil society institutions» concepts are defined, and their evolutionary features and interrelationships are revealed. Scientific approaches to understanding the mechanisms of interaction between public administration bodies and civil society institutions are analyzed.The research employs a complex of general scientific and special methods, including: analysis of scientific literature to determine conceptual approaches to understanding public administration and civil society; structural-functional analysis to reveal the role and place of each interaction subject; comparative method to juxtapose Ukrainian and foreign practices; and axiological approach to highlight the value foundations of state-public partnership.Attention is drawn to the limitations of the current conceptual framework, particularly the inconsistency between the terms «public» and «state» administration in Ukrainian legislation. The necessity of expanding the subject structure of civil society through overcoming public passivity is substantiated.The need to improve communicative mechanisms of interaction, particularly through the implementation of electronic forms of communication, is noted. The potential of civil society institutions as intermediaries between society and public authorities is revealed.Theoretical approaches to optimizing the interaction between public administration bodies and civil society institutions are proposed, specifically through:– Expansion of forms of public participation;– Implementation of democratic governance principles;– Development of communicative mechanisms;– Improvement of regulatory and legal framework.The article emphasizes the prospects for further scientific research on interaction mechanisms between public authorities and civil society in the context of building a democratic state